Predicting Factors of Tuberculosis Preventive Behaviors in Community Among Village Health Volunteers, Udon Thani Province - Wicharit L. (2023)
This study uses a predictive correlational research design. This study aims to analyze the predictability of three common factors: training experience, health literacy, and perception of self-efficacy in tuberculosis (TB) prevention on prevention behaviors in the community of the village health volunteers (VHVs). The samples were obtained from the convenience sampling method. The sample size was determined using the power analysis method and qualified according to the inclusion criteria for a total of 100 people. Data were collected using questionnaires. Data were analyzed using descriptive statistics, Pearson product-moment correlation, and multiple regression analysis. The study revealed that all three factors could predict TB prevention behaviors in the community VHVs in Udon Thani province by 8.8% (R 2 = .088, F (3) = 3.070). Only one variable was able to predict TB prevention behavior in the community with statistical significance. Factors of self-efficacy in TB prevention were statistically predictive of TB prevention behavior in the community (β = .244, p< .05). The findings suggest that government officials involved in the development of VHVs’ capacity should encourage VHVs to recognize their potential and competence in TB prevention, as well as develop health literacy on TB prevention, support TB surveillance training policies, prevention, and control.